1988
DOI: 10.1007/bf00055641
|View full text |Cite
|
Sign up to set email alerts
|

Mating patterns of different Adh genotypes of Drosophila melanogaster I. Differences in mating ability

Abstract: The mating ability of the different Adh genotypes of D. melanogaster, from three natural populations, was estimated as the number of females inseminated by a single male in a 24-hour period. The data indicate that populations of D. melanogaster vary in mating properties, but a common tendency was found in all of them: the heterozygous individuals, especially the males, show a relative advantage with respect to homozygotes. On the other hand, our results suggest that the differences in mating patterns observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies on sexual behaviour in numerous species of Drosophila with particular reference to its genetic control, contribution of two sexes to the variation in mating activity and repeat mating are well documented [1][2][3][4][5][6][7]. It is widely demonstrated that males of different species of Drosophila can inseminate more than one female and mating ability of males is influenced by genetic and other factors [8][9][10][11][12][13]. A male's ability to secure copulations may depend on his phenotype, which can vary according to his physiological condition [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on sexual behaviour in numerous species of Drosophila with particular reference to its genetic control, contribution of two sexes to the variation in mating activity and repeat mating are well documented [1][2][3][4][5][6][7]. It is widely demonstrated that males of different species of Drosophila can inseminate more than one female and mating ability of males is influenced by genetic and other factors [8][9][10][11][12][13]. A male's ability to secure copulations may depend on his phenotype, which can vary according to his physiological condition [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely demonstrated that males of different species of Drosophila can inseminate more than a single female, and the mating ability of males is influenced by genetic and other factors [32,34,36,37]. According to Gromko [12], multiple mating is widely believed to be advantageous for males, and selection of males can produce a correlated response in females.…”
Section: Introductionmentioning
confidence: 99%